Integrasi Teknologi di Gudang Farmasi: Tantangan dan Peluang untuk Meningkatkan Kualitas dan Keamanan Obat - Jajang Japar Sodik; Asep Kamal Sahroni (STIKes Ibnu Sina Ajibarang, 2024)
Pharmaceutical warehouses play a crucial role in maintaining the quality and integrity of medicines within the pharmaceutical supply chain. Proper storage and effective management of these facilities are key to ensuring the effectiveness, safety, and availability of medicines. However, managing pharmaceutical warehouses poses several challenges, such as inventory control, maintaining optimal storage conditions, and detecting genotoxic contaminants, which can impact the quality and availability of medicines. Literature search was conducted across several databases, including PubMed, ScienceDirect, and Google Scholar, using keywords such as